2021
DOI: 10.1002/emp2.12575
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound in predicting COVID‐19 clinical outcomes: A prospective observational study

Abstract: Funding and support: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…The investigators however did not describe individual features of the LUS such as A lines, B lines, and pleural disease and used a high cutoff to optimize sensitivity ( 9 ). In contrast to our findings of pleural irregularities among more severely ill participants, hospital-based cohort in Iran identified pleural thickening to be present in 95% of participants, but the undescribed criteria may have been lower than our greater than or equal to 0.5 cm cutoff ( 18 ). Although other studies have generally used a sum of all 12 lung zones ( 5 , 8 , 9 , 19 , 20 ), our study found the risk estimates were unchanged when some lung fields were not obtainable due to clinical instability.…”
Section: Discussioncontrasting
confidence: 99%
“…The investigators however did not describe individual features of the LUS such as A lines, B lines, and pleural disease and used a high cutoff to optimize sensitivity ( 9 ). In contrast to our findings of pleural irregularities among more severely ill participants, hospital-based cohort in Iran identified pleural thickening to be present in 95% of participants, but the undescribed criteria may have been lower than our greater than or equal to 0.5 cm cutoff ( 18 ). Although other studies have generally used a sum of all 12 lung zones ( 5 , 8 , 9 , 19 , 20 ), our study found the risk estimates were unchanged when some lung fields were not obtainable due to clinical instability.…”
Section: Discussioncontrasting
confidence: 99%
“…Baseline diagnosis can cause several of the LUS findings, but the correlation of LUSS with FiO 2 needed, the differences between disease severity and ventilatory support groups, and the decrease with patient improvement show its usefulness as a monitoring tool. As shown by different publications, LUS is a useful tool in clinical examination and can quantify the loss of aeration at the bedside (29,30). Sequential assessments can help the clinician identify improvement or worsening; thus, they can be used to classify the severity of the disease and follow its progress (31).…”
Section: Discussionmentioning
confidence: 99%
“…While these results suggest clinicians felt the potential advantages of LUS did not consistently outweigh barriers to use in the management of all patients with COVID-19, it is important to note that the perceived barriers are likely dynamic. For instance, lack of evidence for support of LUS in COVID-19 could change with time as there have been multiple studies demonstrating utility in COVID-19 published since our pilot ended [34][35][36]. This may allow a more targeted approach to utilize LUS in the COVID-19 patients who would most benefit.…”
Section: Discussionmentioning
confidence: 99%